A Rare Presentation of Amniotic band syndrome: Antenatal diagnosis and perinatal management - Natchira Winitchai (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2019)
The purpose of this presentation is to report the antenatal diagnosis and perinatal management of an amniotic band syndrome which occurred in the fetus of a pregnant 30-year-old Thai woman who presented at the gestational age of 21 weeks. Mother received regular antenatal care at the antenatal department in a hospital, and had no congenital disease or history of illness with genetic diseases. According to the obstetrician ultrasound examination to assess her gestational age and fetus abnormalities fi nding; right foot sole of the fetus was twisted inwards and there was a large amniotic band floating in the amniotic sac.